Food and Farming under Climate Change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
A high-level event on "Food and Farming Under Climate Change", 8 July 2015 in Paris. The event took place alongside the Our Common Future Under Climate Change conference.